Altered Level of Soluble fms-like Tyrosine Kinase 1 (sFlt1) and Hypoxia Inducible Factor-1alpha (HIF-1alpha) in Normotensive Pregnancy and Preeclampsia - John Wantania; Syakib Bakri; Karel Pandelaki; Maisuri Chalid (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Preeclampsia is still a significant problem worldwide. Of the many suggested mechanisms of its pathogenesis, the latest one is the balance of angiogenic factor and its relationship with hypoxia factors. The objective of this study was to observe changes or dynamic process of soluble fms-like tyrosine kinase 1 (sFlt1) as anti-angiogenic factor and hypoxia inducible factor 1-alpha (HIF-1α) as hypoxia marker in normotensive pregnancy and preeclampsia in mid-term and full-term pregnancies.METHODS: A cohort study was conducted on 36 normotensive subjects, first examination was conducted at 20-28 weeks of gestation. Then second examination was conducted at the time of preeclampsia diagnosed or full-term pregnancy. Preeclampsia was characterized by hypertension of systolic blood pressure ≥140 mmHg, diastolic blood pressure ≥90 mmHg, with two readings separated in 4-6 hours period, and/or proteinuria with urine dipstick of ≥1+ or ≥300 mg per 24 hours. Examinations of sFlt-1 and HIF-1α were done by enzyme-linked immunosorbent assay method. Statistical analysis was done using a significance level of p<0.05.RESULTS: Concentration of sFlt-1 was elevated in normotensive pregnancy and preeclampsia. Higher sFlt-1 concentration elevation was seen in preeclamptic group comparing to normotensive group, although not significant. This finding was related to the fact that investigated subjects were mostly developing mild preeclampsia merely. Comparing to normotensive group, preeclamptic group had higher HIF-1α concentration-per-week elevation, but not significant. There was a positive correlation between concentrations of sFlt-1 and HIF-1α, but not significant.CONCLUSION: sFlt-1 concentration elevation was correlated with preeclampsia. Therefore comparing to averages, changes of sFlt-1 concentrations were more important. Concentrations of HIF-1α and sFlt-1 were positively correlated.KEYWORDS: sFlt-1, HIF-1α, preeclampsia, normotension